Comparison of Refugee Handling Policies from Abroad in Malaysia and Indonesia - Yasir; I Wayan Putu Sucana Aryana; Cokorde Istri Dian Laksmi Dewi (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Currently, there are around 12,295 refugees registered at the UNHCR office in Indonesia. However, many of them have an unclear fate, and many of them have even held demonstrations in various places in Indonesia. The empirical legal research with a comparative approach that was conducted resulted in the following conclusions: a) The chaotic handling of foreign refugees in Indonesia is caused by the negative stigma of the community and government towards the existence of foreign refugees, institutional problems, and socio-economic conditions that do not support facilitating employment opportunities for foreign refugees; b) Indonesia and Malaysia are not obliged to accept refugees because they are not signatories to the 1951 Refugee Convention and the 1967 Refugee Protocol. However, the two countries continue to accept them temporarily for humanitarian reasons. The system for handling foreign refugees in Malaysia is more controlled because the legal system adopted also influences Malaysia's firm stance towards foreign refugees. The government must immediately improve the mechanism for handling asylum seekers and foreign refugees in Indonesia so that institutional problems can be overcome and create a more focused handling system that is able to form a firm stance regarding the existence of foreign refugees in Indonesia.